Life storytelling at the ABC: Challenges of ‘giving the audience a voice’ in the context of public service media - Mackay Sasha; Heck Elizabeth (Cultural Science)
Life storytelling projects have become an important means through which public service media institutions such as the Australian Broadcasting Corporation are seeking to foster audience participation and involve particular cohorts in the creation and distribution of broadcast content. This paper contributes to the wider conversation on audience participation within public service media intuitions (PSMs), and focuses on the opportunities and challenges that arise within life storytelling projects that are facilitated by these institutions, and that aim to ‘give voice’ to members of ‘the audience’. In particular, it focuses on two of the Australian Broadcasting Corporation’s current life storytelling projects: ABC Open and Heywire.